Democracy in the third world - Pinkney, Robert (Issues in third world politics, 1993)
"Today, the majority of the world's governments have been chosen by meals of competitive elections - quite a different state of affairs than the one found just twenty years ago. Robert Pinkney explores this transformation, seeking to explain the reasons for and significance of the emergence, or reemergence, of democratic regimes." "After considering what is meant by "democracy", Pinkney examines the debates on the conditions conducive to its emergence in the Third World. This leads to the question of whether new explanations of democratic development are needed. Subsequent chapters analyze the varied effects of colonial rule, the fate of incipient democracies superseded by authoritarianism, and the exceptional cases where democracy has survived continuously since independence. The final chapter of the book assesses future prospects for democracy in the Third World."--BOOK JACKET.